2003
DOI: 10.1210/jc.2003-030457
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Extracellular Matrix Metalloproteinase Inducer in Human Endometrium during the Menstrual Cyclein Vivoandin Vitro

Abstract: Extracellular matrix metalloproteinase inducer (EMMPRIN) participates in the breakdown of the extracellular matrix (ECM) by augmenting matrix metalloproteinase (MMP) expression. In the present study, we identified and characterized the menstrual cycle-dependent expression of EMMPRIN in human endometrium in vivo. At the proliferative phase of the menstrual cycle, EMMPRIN was detected in glandular epithelium of the basal layer in endometrium. In addition, at the superficial region of the functional layer, EMMPRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 59 publications
3
48
1
Order By: Relevance
“…Differential modification of EMMPRIN through glycosylation may be cell-type specific or associated with malignancy of cells. Alternatively, as there is evidence reported in the literature suggesting that posttranslational modification of EMM-PRIN might be regulated by hormones, 44 it is tempting to speculate that differential modification of the EMMPRIN polypeptide preferentially may occur in hormone-dependent cell types. However, the mechanisms controlling differential glycosylation of EMMPRIN still remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Differential modification of EMMPRIN through glycosylation may be cell-type specific or associated with malignancy of cells. Alternatively, as there is evidence reported in the literature suggesting that posttranslational modification of EMM-PRIN might be regulated by hormones, 44 it is tempting to speculate that differential modification of the EMMPRIN polypeptide preferentially may occur in hormone-dependent cell types. However, the mechanisms controlling differential glycosylation of EMMPRIN still remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The laminin receptors α1β1, α6β1 and α7β1 are likely to be important at this stage. Furthermore, the integrin β1 interactor CD147 (EMMPRIN, officially known as basigin) is required for optimal implantation (Igakura et al, 1998;Kuno et al, 1998;Lee et al, 2013;Noguchi et al, 2003;Xiao et al, 2002).…”
Section: Integrin Expression and Activation In The Blastocystmentioning
confidence: 99%
“…EMMPRIN is expressed on the cell surface of various tumors and some normal tissues/cells such as uterine endometrium, macrophages, and T-lymphocytes (1,(3)(4)(5). Many investigators have reported that increased EMMPRIN expression causes the augmentation of matrix metalloproteinases (MMPs)-1, -2, and -3, and membrane-type MMP (MT-MMP) expression in peritumoral stoma cells, and thereby increases tumor invasiveness in vivo and in vitro (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%